2006
DOI: 10.1111/j.1467-9817.2006.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on reading and listening comprehension

Abstract: We report preliminary behaviour genetic analyses of reading and listening comprehension from The Colorado Learning Disabilities Research Center. Although the twin sample with these new measures is still of limited size, we find substantial, and significant, genetic influences on individual differences in both reading and listening comprehension. In addition, word recognition and listening comprehension each accounted for significant independent genetic influences on reading comprehension. Together, they accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
142
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(162 citation statements)
references
References 40 publications
19
142
0
1
Order By: Relevance
“…However, our results are consistent with those of Keenan, Betjemann, Wadsworth et al (2006) and Wadsworth et al (2001Wadsworth et al ( , 2006, who found negligible shared environmental influences in older children. Moreover, even in much younger children, Byrne and colleagues also report that shared environmental effects found in kindergarten were no longer significant by the end of first grade (Byrne et al, 2007).…”
Section: Environmental Effectssupporting
confidence: 92%
See 3 more Smart Citations
“…However, our results are consistent with those of Keenan, Betjemann, Wadsworth et al (2006) and Wadsworth et al (2001Wadsworth et al ( , 2006, who found negligible shared environmental influences in older children. Moreover, even in much younger children, Byrne and colleagues also report that shared environmental effects found in kindergarten were no longer significant by the end of first grade (Byrne et al, 2007).…”
Section: Environmental Effectssupporting
confidence: 92%
“…Between measures, a high proportion of the covariance of reading comprehension and word reading was due to shared genetic factors, but we also noted a significant genetic factor unique to reading comprehension at both time points, independent of word reading. This supports the recent findings of Keenan and colleagues (Keenan, Betjemann, Wadsworth et al, 2006), who also observed a unique genetic factor for reading and listening comprehension. It suggests that while many of the genetic influences on reading comprehension and word reading are overlapping, there are unique genetic influences on comprehension processes, supporting the argument that reading comprehension skills may be unique and separable from word reading skills (e.g., Cain et al, 2000;Catts et al, 2003;Gough et al, 1996;Gough & Tunmer, 1986;Hoover & Gough, 1990;Leach et al, 2003;Nation, 2005;Oakhill et al, 2003).…”
Section: Continuity Of Genetic Effectssupporting
confidence: 92%
See 2 more Smart Citations
“…Reading ability will impact the difficulty of the primary object-level task of text processing. Some readers struggle with one or more of the subprocesses involved in comprehension (e.g., Keenan, Betjemann, Wadsworth, DeFries, & Olson, 2006;Perfetti, 1985;Yuill & Oakhill, 1991). Thus, they should be limited in their ability to concurrently carry out the task of monitoring.…”
mentioning
confidence: 99%